THE RELATIONSHIP BETWEEN DEMOCRACY AND BUREAUCRATIC PROFESSIONALISM IN INDONESIA - Putra, Rismana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Bureaucratic reform that began in Indonesia since 1998 has become a crucial moment in the effort to build a democratic and professional government. This study aims to explore the relationship between democracy and professionalism in the bureaucracy by highlighting the challenges and opportunities that arise within the framework of government reform. Using a qualitative descriptive approach, data were collected through a literature review of relevant regulations, policies, and previous research. The results of the study indicate that professionalism in the bureaucracy is an important foundation to support successful democratic practices, especially in the provision of fair and transparent public services. However, the politicization of the bureaucracy, the implementation of a weak merit system, and resistance to change are serious obstacles to realizing a neutral and competent bureaucracy. Therefore, the integration of democratic values into the structure and culture of the bureaucracy is an important requirement for creating responsible governance that supports the interests of the community.